EFFECT OF TILLERS REMOVAL AND NITROGEN LEVELS ON SOME GROWTH TRAITS OF TWO BREAD WHEAT VARIETIES - & et al., Jaddoa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted at the experimental field of field Crop Dept.- Coll. of Agric.Univ. of Baghdad, during the winter season 2012– 2013 to investigate the effect of tillers removing on some growth traits under two nitrogen levels for two wheat varieties This experiment was carried out by using Randomized Complete Block Design with in  split– split plot arrangement with three replicats. IPA 99 and Abu– Ghraib 3 were assigned in main plots, nitrogen levels (100,200) kg.ha-1 occupied sub- plot, while tillers reamoving treatment (reamove the main stem, first tiller, second tiller, and third tiller) occupied the sub– sub plots. The results revealed, that IPA 99 and 200 kg.ha-1 were superior in all growth traits. The main stem removing increased significantly number of tillers, dry weight, crop growth rate and realativ growth rate, while first tiller reamoving increased plant hight, flag leaf area, chlorophell content and dry weight of flag leaf area 91.18 cm, 36.81 cm2 59.95 Mgm.cm-3 and 0.456 gm respectively in contrast with the main stem removing which gave 68.88 cm, 27.87 cm2, 47.81 Mgm.cm-3, and 0.266 gm respectively. It could be conclude that relationship between the main stem and tillers was competitive.